2015
DOI: 10.1007/s00359-015-1055-y
|View full text |Cite
|
Sign up to set email alerts
|

Bumblebee flight performance in environments of different proximity

Abstract: Flying animals are capable of navigating through environments of different complexity with high precision. To control their flight when negotiating narrow tunnels, bees and birds use the magnitude of apparent image motion (known as optic flow) generated by the walls. In their natural habitat, however, these animals would encounter both cluttered and open environments. Here, we investigate how large changes in the proximity of nearby surfaces affect optic flow-based flight control strategies. We trained bumbleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…The walls of the flight tunnel were lined with a black-and-white pattern to enable a direct comparison with the previous studies that used the same arrangement (e.g., Linander et al 2015, 2016). To minimize lateral optic flow input, the walls displayed a uniform grey pattern.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The walls of the flight tunnel were lined with a black-and-white pattern to enable a direct comparison with the previous studies that used the same arrangement (e.g., Linander et al 2015, 2016). To minimize lateral optic flow input, the walls displayed a uniform grey pattern.…”
Section: Methodsmentioning
confidence: 99%
“…The floor of the flight tunnel was white or lined with a red-and-white dead leaves pattern that facilitated the tracking of the bees in the recorded sequences while still maintaining a high pattern contrast. We lined the floor with white to enable comparison with earlier studies (e.g., Linander et al 2015, 2016). Figure 1 illustrates the different experimental conditions for one tunnel width.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…This was investigated in honeybees and bumblebees flying through experimental tunnels, in which patterns on the walls of provided optic cues (e.g., [68,89,90]. Bees estimate flight distance using only the green receptor contrast of the patterns, independent of chromatic contrast and brightness contrast [91], and because translational optic flow depends on distance, the estimate depends on the distance of bees to the contrasting patterns (e.g., [92]). Bees also use optic flow to control flight speed and flight height [93], and to avoid flying too close to obstacles, by balancing the optic flow on both sides (e.g., [64,89]).…”
Section: Flight Ranges and Flight Controlmentioning
confidence: 99%
“…It is interesting to note that bumblebees, when flying in very wide tunnels lined with patterns inducing strong translational optic flow (120 and 240 cm width), also display a large variation in flight speed (Linander et al, 2016)even larger than that observed in hawkmoths. Thus, the regulation of flight speed by lateral optic flow cues might depend on the perceived relative proximity of the environmentand this might differ for different insect species.…”
Section: Control Of Flight Speed By Translational Optic Flowmentioning
confidence: 99%